Asuhan Keperawatan Pada Ny. K Dengan Post Operasi Sectio Caesarea Indikasi Janin Terlilit Tali Pusat Di Ruang Nusa Indah RSUD Dr. Soeselo Kabupaten Tegal - Tri Yulianti; Tati Karyawati; Siti Fatimah (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
According to Rahmi (2019) in Rimadeni et al. (2022), Sectio Caesarea (SC) is the act of removing the fetus and placenta by making an incision in the abdominal wall and uterus. SC can be an alternative delivery both for causes from the mother and from the fetus, one of which is because the fetus is entangled in the umbilical cord. The purpose of this writing is to find out and provide nursing care to Mrs. K in Nusa Indah Room, dr. Soeselo Hospital, Tegal Regency according to nursing standards. The method used is descriptive observation with a nursing process approach. From the case review, it was found that the client's main complaint was acute pain in the incision wound. There were three nursing diagnoses found, namely acute pain, risk of infection, and knowledge deficit. Interventions are prepared based on the theory of SLKI and SIKI as well as on the client's condition, and can be implemented. Based on the evaluation carried out on the client, two problems were resolved and one problem was partially resolved. During the research, the author found gaps in theory and data studied from patients